Plastic flow and failure in single point incremental forming of PVC sheets - P. A. F. Martins; S. Alkas Yonan; M. B. Silva; A. E. Tekkaya (eXPRESS Polymer Letters)
This paper presents an innovative and effective methodology to characterize plastic flow and failure in single point incremental forming (SPIF) of polymers that allows determining the stresses and the accumulated values of ductile damage directly from the experimental values of strain at various positions over the deformed polymer sheets. The approach traces the deformation path of material elements in conical and pyramidal SPIF parts, undergoing linear strain loading paths from beginning until failure, and is built upon the generalization of the analytical framework conditions assumed by Glover et al. [1] to the pressure-sensitive yield surfaces of polymers under incompressible, non-associated, plastic flow. Experimentation in conventional and multi-stage SPIF of Polyvinylchloride (PVC) sheets confirms the effectiveness of the proposed methodology and demonstrates that standard non-coupled damage models currently utilized in sheet metal forming are inapplicable to describe failure in polymers. Instead fracture forming limit lines (FFL’s) should be employed.